Contemporary Higher Education: An Environment Ripe for Corruption - Denisova-Schmidt, Elena; de Wit, Hans; Altbach, Philip (International Higher Education, 2025)
The global competition for rankings and the current geopolitical challenges are just two of the issues fueling corruption in higher education in various forms, including data manipulation, biased recruitment, unethical authorship, and other problems eroding integrity and transparency. Since cultural norms and other systemic pressures can blur ethical boundaries, it is crucial to explore the causes, cultural dimensions, and reforms needed to restore accountability and ethical governance.